EXPLORING THE PRESERVICE TEACHERS’PERCEPTION TOWARD THE USE OF DUOLINGO IN TEACHING VOCABULARY TO YOUNG LEARNERS - Dwi Ima Herminingsih (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
The purpose of doing research is to have the investigation on the students’ belief when Duo lingo application is applied in the class of vocabulary and to describe the justification of the advantages using the Duo lingo to empower the vocabulary enrichment. The students of English Study Program in State Islamic College as Pre Service –teachers have participated in this study. The data were collected by the questionnaire distribution and the interview methods. The data analysis uses the qualitative description. The result of the study exposes the facts that the respondents agree the Duo lingo can facilitate the vocabulary learning achievement. The medium labelled Duo lingo makes the students easy and interesting in learning the English word knowledge. The interview with the sample of informants suggests the testimony that the young learners can use the app overtime as far as they want. They are free to set or make up the schedule of lesson session. One more meaningful thing found in the application is that the English is spoken by the native speaker. By performing the English of the native speaker can be a model or master for the students. They get the chance to exercise repeating the word or the sentence spoken by the native speaker correctly.